HUBUNGAN PENGETAHUAN DAN SIKAP REMAJATERHADAP UPAYA PEMUTUSAN MATA RANTAI PENULARAN COVID-19 DI PANGKALAN KASAI KABUPATEN INDRAGIRI HULU RIAU - Franticha, Nandhitha Succy; Anggreni, Elsie; Rahayu, Restianingsih Putri (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2021)
Covid-19 is caused by SARS-Co-V a new type of coronavirus virus that infects the respiratory system. The purpose of this study is to find out the relationship of knowledge and attitudes of young adult to efforts to break the chain of transmission of covid-19 in Pangkalan Kasai. The method used is an analytical method with probability Sampling techniques. The results of the study on the relationship of knowledge and attitude of adolescents to the efforts to break the chain of transmission of covid-19 in Pangkalan Kasai obtained the results of adolescents who have enough knowledge as much as 62,7%, knowledgeable 28% and knowledgeable less 9,.3%. The results of the measurement of adolescent attitudes obtained negative results as much as 45,3% and positive as much as 54,7%. While the results of measurement efforts showed that 65,3% to break the chain of covid-19 transmission. The conclusion is that there is a significant relationship between adolescent knowledge of efforts to break the chain of covid-19 with a P Value of 0,012 and there is no signficant relationship between adolescent attitudes towards efforts to break the chain of transmissions of covid-19 in Pangkalan Kasai 2021.